The Role of Product Innovation in MSME Sustainability: A Review from an Entrepreneurial Perspective - Imam Jayanto; Dian Parwati; Surya Sumantri Abdullah; Irma Antasionasti (ADMAN: Journal of Contemporary Administration and Management, 2026)
This study aims to analyze the role of product innovation in supporting the sustainability of Micro, Small, and Medium Enterprises (MSMEs) from an entrepreneurial perspective. The study employs a literature review method using a qualitative approach and descriptive analysis. Data were collected from Google Scholar, ScienceDirect, MDPI, and publications from credible institutions covering the period 1964–2026. A total of 68 articles were identified during the initial stage and subsequently screened based on relevance, quality, and topic suitability, resulting in 43 articles being selected as the primary sources for analysis. The findings indicate that product innovation plays a significant role in enhancing competitiveness, strengthening customer loyalty, expanding market opportunities, and improving MSMEs' adaptive capacity to changes in the business environment. From an entrepreneurial perspective, creativity, innovation orientation, dynamic capabilities, and collaboration are identified as key factors that reinforce business sustainability. This review confirms that product innovation is a strategic instrument for MSMEs to maintain business continuity while fostering sustainable growth.